Developing Climate-Resilient, Direct-Seeded, Adapted Multiple-Stress-Tolerant Rice Applying Genomics-Assisted Breeding - Sandhu, Nitika; Yadav, Shailesh; Catolos, Margaret; Cruz, Ma Teresa Sta; Kumar, Arvind (Frontiers in Plant Science, 2021)
Breeding for dry direct-seeded adapted rice varieties is an urgent need to address the emerging scenario of water–labor shortage. The aim of this study was to develop high-yielding, direct-seeded adapted varieties utilizing biparental to multiparental crosses involving as many as 6 different parents in conventional and 12 parents in genomics-assisted breeding programs. The rigorous single plant selections were followed from the F2 generation onwards utilizing phenotypic selection and quantitative trait locus (QTL)/gene based/linked markers for tracking the presence of desirable alleles of targeted QTL/genes. In conventional breeding, multiparent lines had significantly higher yields (2072 to 6569 kg ha-1) than the biparental lines (1493 to 6326 kg ha-1). GAB lines derived from multiparent crosses had significantly higher (3293 to 6719 kg ha-1) yield than the multiparent lines from conventional breeding (2072 to 6569 kg ha-1). Eleven promising lines from genomics-assisted breeding carrying 7–11 QTL/genes and eight lines from conventional breeding with grain-yield improvement from 727 to 1705 kg ha-1 and 68 to 902 kg ha-1, respectively, over the best check were selected. The developed lines may be released as varieties/parental lines to develop better rice varieties for direct-seeded situations or as novel breeding material to study genetic interactions.